Retention Among North American HIV–infected Persons in Clinical Care, 2000–2008 - Rebeiro, Peter (2013)
BACKGROUND: Retention in care is key to improving HIV outcomes. Our goal was to describe “churn” in patterns of entry, exit, and retention in HIV care in the US and Canada. METHODS: Adults contributing ≥1 CD4 count or HIV-1 RNA (HIV-lab) from 2000–2008 in North American Cohort Collaboration on Research and Design (NA-ACCORD) clinical cohorts were included. Incomplete retention was defined as lack of 2 HIV-labs (≥90 days apart) within 12 months, summarized by calendar year. We used beta-binomial regression models to estimate adjusted odds ratios (OR) and 95% confidence intervals (CI) of factors associated with incomplete retention. RESULTS: Among 61,438 participants, 15,360 (25%) with incomplete retention significantly differed in univariate analyses (p<0.001) from 46,078 (75%) consistently retained by age, race/ethnicity, HIV risk, CD4, ART use, and country of care (US vs. Canada). From 2000–2004, females (OR=0.82, CI:0.70–0.95), older individuals (OR=0.78, CI:0.74–0.83 per 10 years), and ART users (OR= 0.61, CI:0.54–0.68 vs all others) were less likely to have incomplete retention, while black individuals (OR=1.31, CI:1.16–1.49, vs. white), those with injection drug use (IDU) HIV risk (OR=1.68, CI:1.49–1.89, vs. non-IDU) and those in care longer (OR=1.09, CI:1.07–1.11 per year) were more likely to have incomplete retention. Results from 2005–2008 were similar. DISCUSSION: From 2000 to 2008, 75% of the NA-ACCORD population was consistently retained in care with 25% experiencing some change in status, or churn. In addition to the programmatic and policy implications, our findings identify patient groups who may benefit from focused retention efforts.